2015
DOI: 10.1111/trf.13356
|View full text |Cite
|
Sign up to set email alerts
|

Five‐day stability of thawed plasma: solvent/detergent‐treated plasma comparable with fresh‐frozen plasma and plasma frozen within 24 hours

Abstract: BACKGROUND Plasma stored refrigerated for up to 5 days after thawing is common practice in many US hospitals. Therefore, clotting factor activities in fresh‐frozen plasma (FFP), plasma frozen within 24 hours (PF24), and solvent/detergent‐treated plasma (SDP), thawed and stored at 1 to 6°C for up to 5 days, were investigated. STUDY DESIGN AND METHODS Five A, B, O, and AB units of FFP, PF24, and SDP were thawed and maintained for 5 days at 1 to 6°C. The activity of factor (F)V, FVII, FVIII, protein S (PS), and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 14 publications
4
27
0
Order By: Relevance
“…Sidhu et al also found no change in fibrinogen or FVII levels between Days 1 and 5 of refrigerated storage and a statistically significant loss of FV activity, mirroring our results [23]. Similarly, Neisser-Svae et al found residual FVIII activities in thawed FFP of 0.75 ± 0.13 IU/mL (mean ± SD) after 5 days of refrigerated storage [24], and von Heymann et al reported median FVIII values of 0.75 with an interquartile (25–75%) range of 0.68 to 0.88 IU/mL for thawed FFP, again showing strong similarity to our results with ACD-FFPA [25]. …”
Section: Discussionsupporting
confidence: 87%
“…Sidhu et al also found no change in fibrinogen or FVII levels between Days 1 and 5 of refrigerated storage and a statistically significant loss of FV activity, mirroring our results [23]. Similarly, Neisser-Svae et al found residual FVIII activities in thawed FFP of 0.75 ± 0.13 IU/mL (mean ± SD) after 5 days of refrigerated storage [24], and von Heymann et al reported median FVIII values of 0.75 with an interquartile (25–75%) range of 0.68 to 0.88 IU/mL for thawed FFP, again showing strong similarity to our results with ACD-FFPA [25]. …”
Section: Discussionsupporting
confidence: 87%
“…We thank Neisser-Svae and Heger for their interest in the addendum publication (Green et al, 2017), and for sharing their data of thawed solvent detergent-treated fresh frozen plasma (SDFFP) for up to 5 days (Neisser-Svae et al, 2016). We agree with the authors that the reduction in factor VIII (FVIII) for 5 days following thawing is not significantly different between SDFFP and fresh frozen plasma (FFP).…”
Section: Author Contributionssupporting
confidence: 59%
“…Although the solvent/detergent (S/D) treated FFP (Octaplas) is not considered in this addendum, we would like to bring to the readers' attention that a 5-day stability study comparing Octaplas to FFP has recently been published (Neisser-Svae et al, 2016). In this study, in addition to the activity level of factor (F)V and FVII, the change in the activity of the procoagulant labile FVIII during storage was investigated.…”
mentioning
confidence: 99%
“…After thawing, FV activity in FFP decreases from 1.11 ± 0.22 IU/mL on Day 0 to 0.66 ± 0.15 IU/mL on Day 5, representing a 40% decrease. When SDP is thawed, FV activity decreases from 1.20 ± 0.14 IU/mL on Day 0 to 0.85 ± 0.06 IU/mL, representing only a 29% decrease …”
Section: Discussionmentioning
confidence: 99%